Neddylation Regulates Macrophages and Implications for Cancer Therapy - Jiang, Yanyu; Li, Lihui; Li, Yan; Liu, Guangwei; Hoffman, Robert M.; Jia, Lijun (Frontiers in Cell and Developmental Biology, 2021)
Tumor-associated macrophages (TAMs) promote cancer progression via stimulating angiogenesis, invasion/metastasis and suppressing anti-cancer immunity. Targeting TAMs is a potential promising cancer therapeutic strategy. Neddylation adds the ubiquitin-like protein NEDD8 to substrates, and thereby regulates diverse biological processes in multiple cell types, including macrophages. By controlling cellular response, the neddylation pathway regulates the function, migration, survival and polarization of macrophages. In the present review we summarized how the neddylation pathway modulates TAMs and its implications in cancer therapy.